COMMUNITY STRUCTURE OF BIVALVE IN THE COASTAL WATERS OF NAGALAWAN VILLAGE, PERBAUNGAN DISTRICT, SERDANG BEDAGAI REGENCY, NORTH SUMATERA PROVINCE - Sitompul, Krivide; Samiaji, Joko; Tanjung, Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Bivalve is benthic animal that lives on the bottom and surface of aquatic substrate. The community structure of bivalves is influenced by the changes in environmental factors. This research was conducted in July-August 2018 in the coastal waters of Nagalawan Village, Perbaungan District, Serdang Bedagai Regency, North Sumatera Province.The aims of the research were to determine the structure of the bivalve community which includes species, abundance, relative abundance, diversity index, uniformity index, dominance index and distribution patterns. Sampling used the line transect method at 3 stations. The results of the study found 9 bivalve families consisting of 11 species. The abundance value obtained was in the range of 4.22-7.30 ind./m2. Diversity index values ranged from 1.21-1.6, which are classified as moderate, while the uniformity index value ranges from 0.18-0.26 which is unbalanced. The dominance index value ranged from 0.38-0.5, i.e there are species that dominate. The distribution pattern values ranged from 3.03-3.07 with clustered distribution patterns. Keywords: Bivalves, Community Structure, Nagalawan Village